Never say die - Horowitz, Anthony, 1955- (Horowitz, Anthony, 1955- Alex Rider adventure., 2017)
Fifteen-year-old MI6 agent Alex Rider travels around the world on a dangerous mission to destroy the deadly terrorist organization, Scorpia, once and for all.